How do personality and motivation affect the oral proficiency of the Advanced English I students of semester II 2012 at the Foreign Languages Department? - Orellana Domínguez, Lissette Magdalena; Mejía Solórzano, Vilma Alejandra; Mejía Quintanilla, Manuel Alejandro; Díaz Rivas, Krissia Jeannette; Hernández Rivas, René Arturo; Garay Salinas, Ricardo (San Salvador. El Salvador : Universidad de El Salvador, 2013)
Speaking has been regarded as the most important skill when learning a second language. This has been part of many researches; some of them agree that personality and motivation have an influence on achieving certain level of oral proficiency. Researchers classify personality in two types: extroversion and introversion. Most of the researchers agree that extrovert students are the ones who always achieve a high level of English, and therefore, the highest level of oral proficiency. The aim of this research was investigating how personality and the level of motivation affect the oral proficiency of Advanced English I students of the semester II 2012 at the Foreign Languages Department. By analyzing the data obtained, it was concluded that students’ personality type, on one hand, does not affect students’ oral proficiency level because both, extroverts and introverts, have the same probabilities of achieving a specific level of proficiency. The level of motivation, on the other hand, plays an important role on this process since highly motivated students have more chances of becoming more orally proficient than lowly motivated ones. Factors such as, gender, learning strategies, and teaching methods could have influenced these results, and this was suggested for further research.
Anexos
Tesis -- (Licenciado en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliografía : hojas 37-38
Keywords: Inglés -- Enseñanza; Comunicación oral; Personalidad; Motivación